2012
DOI: 10.1111/j.1600-051x.2012.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Crestal bone resorption after the application of two periodontal surgical techniques. A randomized, controlled clinical trial

Abstract: Bone resorption of the alveolar crest is a phenomenon that is observed as a consequence of periodontal surgical treatment without significant differences between the two techniques. Furthermore, both surgical techniques lead to satisfactory clinical results, indicating that bone removal during periodontal surgical treatment is not always necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…In addition, a conservative moderate correlation of r = 0.30 between before-after measurements was anticipated. This difference of 1 mm is in accordance with the current literature (15), considering that the expected SD of the before-after differences will be approximately 1 mm. A priori power analysis was accomplished using the G*Power v.3.1.0 software (16).…”
Section: Subject Samplesupporting
confidence: 92%
“…In addition, a conservative moderate correlation of r = 0.30 between before-after measurements was anticipated. This difference of 1 mm is in accordance with the current literature (15), considering that the expected SD of the before-after differences will be approximately 1 mm. A priori power analysis was accomplished using the G*Power v.3.1.0 software (16).…”
Section: Subject Samplesupporting
confidence: 92%
“…Our results showed that after 6 months of therapeutic procedures, the topical use of ALN promoted beneficial effects similar to the findings of Sharma and Pradeep with the same follow‐up time, similar clinical evaluation, except from the analysis of the bone defect by DSR. In this sense, the use of DSR in our study promoted an increase in the sensitivity and specificity of the images …”
Section: Discussionmentioning
confidence: 68%
“…Histological study in humans has demonstrated that alveolar crest bone loss may be a consequence of surgical periodontal treatment and is associated with trauma and the periodontal biotype . It is worth mentioning that Kyriazis et al . demonstrated similar bone crest reabsorption rates using DSR when comparing to two periodontal surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the defect angle may also be partially a mathematical function of defect depth, since it has been shown that narrow defect angles are related to deep intrabony defects (Kim et al 2006). The suprabony defect depth increase is of a smaller magnitude than the crestal bone resorption observed after periodontal surgical treatment, generally shown to range from 0.8 mm to 1.7 mm (Persson et al 2000, Kyriazis et al 2012, although smaller values have also been observed (Joly et al 2002). Both widening of the defect angle and increase in suprabony defect depth are probably expressions of the significant bone remodelling which clearly takes placed in intrabony defects after MINST.…”
Section: Discussionmentioning
confidence: 99%